2000
DOI: 10.1097/00002030-200010200-00005
|View full text |Cite
|
Sign up to set email alerts
|

Shift in HIV resistance genotype after treatment interruption and short-term antiviral effect following a new salvage regimen

Abstract: Suspending treatment for 3 months after multiple failures could be a suitable strategy for optimizing salvage therapy provided it is instituted early, before the HIV disease becomes too advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 35 publications
2
63
3
Order By: Relevance
“…It was previously reported that not all the patients with treatment failure undergoing STI experienced a reversal in their drug-resistance-associated genotype (10,12,16,26,45,59). Elucidating the factors that could predict which patients would revert from their drug-resistant genotype to a drug- sensitive one after STI would be of great use for the physicians managing patients with ARV treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that not all the patients with treatment failure undergoing STI experienced a reversal in their drug-resistance-associated genotype (10,12,16,26,45,59). Elucidating the factors that could predict which patients would revert from their drug-resistant genotype to a drug- sensitive one after STI would be of great use for the physicians managing patients with ARV treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…When this selective pressure is removed, the emergence of drug-sensitive quasispecies may be expected, as they would be predicted to have a higher fitness in a drug-free environment (9,15,19,20,22,25,34,40,42,43). This rationale led to the many structured treatment interruption (STI) studies carried out on patients with treatment failure and multidrug-resistant viruses (10,12,16,26,45,59). In those cohorts, a rise in plasma viral load and a concomitant fall in CD4 ϩ cell count was observed after treatment interruption; in approximately half of the patients, drug susceptibility shifted from resistant to sensitive.…”
mentioning
confidence: 99%
“…Two cohorts were evaluated: patients at Hôpital Bichat-Claude Bernard, Paris, France (kinetic studies), and patients participating in a clinical trial of a 3-month STI performed at Centre Hospitalier Universitaire (CHU) Purpan, Toulouse, France. Clinical aspects and outcome of this trial have been presented elsewhere (20). All patients gave informed consent before undertaking STI.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, these adaptations have allowed the programme to scale up from initially few monthly inclusions (mean 16 12 For viral loads greater than 1000 copies per mL, HIV-1 reverse transcriptase genotyping and identifi cation of HIV subtypes were undertaken at the same time. 13,14 The resistance profi les to antiretroviral molecules were defi ned according to National Agency for AIDS Research (ANRS) algorithms. 15 Ethics approval for the survey was obtained from the ethics committee of the Malawi Ministry of Health and written consent was obtained from all participants.…”
Section: Treatmentmentioning
confidence: 99%